A novel stem cell type at the basal side of the subventricular zone maintains adult neurogenesis - Baur, Katja; Abdullah, Yomn; Mandl, Claudia; Hölzl-Wenig, Gabriele; Shi, Yan; Edelkraut, Udo; Khatri, Priti; Hagenston, Anna M; Irmler, Martin; Beckers, Johannes; Ciccolini, Francesca (EMBO reports, 2022)
According to the current consensus, murine neural stem cells (NSCs) apically contacting the lateral ventricle generate differentiated progenitors by rare asymmetric divisions or by relocating to the basal side of the ventricular–subventricular zone (V-SVZ). Both processes will ultimately lead to the generation of adult-born olfactory bulb (OB) interneurons. In contrast to this view, we here find that adult-born OB interneurons largely derive from an additional NSC-type resident in the basal V-SVZ.
Gesehen am 26.10.2022